Effects of TNF-α-308G/A Polymorphism on the Risk of Diabetic Nephropathy and Diabetic Retinopathy: An Updated Meta-Analysis - Liu, Mengwei; Shang, Mengke; Wang, Yue; Li, Qian; Liu, Xiuping; Yang, Luping; Zhang, Qian; Zhang, Kaili; Liu, Shan; Nie, Fangfang; Zeng, Fanxin; Wen, Youhan; Liu, Wanyang (Hormone and Metabolic Research, 2020)
Diabetic nephropathy (DN) and diabetic retinopathy (DR) are the major factors of morbidity and mortality in the patients with diabetes mellitus (DM). Growing studies have investigated the relationship between the TNF-α-308G/A polymorphism and the susceptibility to DN and DR, without achieving consensus. Thus, we conducted this meta-analysis to reach more comprehensive conclusions for these issues. Eligible studies were retrieved through electronic databases such as PubMed, Embase, Web of Science and China National Knowledge Infrastructure. Summary of odds ratios (OR) and 95% confidence intervals (CIs) were generated to evaluate the intensity of the associations. Statistical analyses were performed by STATA 11.0 and RevMan 5.2. There are fourteen eligible publications involving nineteen studies in this meta-analysis. TNF-α-308G/A polymorphism was significantly related to increasing risk of DN under recessive model (OR=1.37, 95% CI=1.03–1.83) and homozygous model (OR=1.54, 95% CI=1.15–2.06). Moreover, the similar results were also obtained in Asian groups for DN (recessive: OR=1.69, 95% CI=1.18–2.42; homozygous: OR=1.99, 95% CI=1.38–2.86; respectively), and significant association was also detected between TNF-α-308G/A and DN susceptibility in type 2 DM in recessive model (OR=1.39, 95% CI=1.02–1.89). No significant association was observed between TNF-α-308G/A and DR susceptibility in total analyses and subgroup analyses by ethnicity and type of DM. TNF-α-308G/A polymorphism may enhance the susceptibility to diabetic nephropathy, especially in Asian population and in T2DM patients, but not diabetic retinopathy.
Keywords: TNF-a-308G/A; polymorphism; meta-analysis; diabetic nephropathy; diabetic retinopathy; genetic models